2019
DOI: 10.3390/atmos10110641
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds in a Petrochemical Region in Arid of NW China: Chemical Reactivity and Source Apportionment

Abstract: We measured volatile organic compounds (VOCs) during the heating, non-heating, and sandstorm periods in the air of the Dushanzi district in NW China and investigated their concentrations, chemical reactivity, and sources. The observed concentrations of total VOCs (TVOCs) were 22. 35 ± 17.60, 33.20 ± 34.15, and 17.05 ± 13.61 ppbv in non-heating, heating, and sandstorm periods, respectively. C 2 -C 5 alkanes, C 2 -C 3 alkenes, benzene, and toluene were the most abundant species, contributing more than 60% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Previous experiments have shown that C4 and C5 SCCPs, such as n-butane, isobutane, and propane, are the main substances in LPG and NG (Huang and Hsieh, 2019). Additionally, isopentane and n-pentane are indicators of gasoline vehicle exhaust (Xiaoxiao Zhang et al, 2019). Therefore, factor 4 originated from traffic.…”
Section: Source Apportionment Of Vocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that C4 and C5 SCCPs, such as n-butane, isobutane, and propane, are the main substances in LPG and NG (Huang and Hsieh, 2019). Additionally, isopentane and n-pentane are indicators of gasoline vehicle exhaust (Xiaoxiao Zhang et al, 2019). Therefore, factor 4 originated from traffic.…”
Section: Source Apportionment Of Vocsmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are precursors of photochemical ozone (O 3 ) (He et al, 2019) and their concentration and reactivity have important effects on O 3 formation (Huang and Hsieh, 2019). VOCs ubiquitous in the atmospheric environment and also act as important precursors in urban atmospheric chemical reactions (Zhang et al, 2019). They undergo a series of complex steps, particularly under solar ultraviolet radiation, and react with certain chemical components in the air to form secondary pollutants (such as O 3 , peroxyacetyl nitrate (PAN), secondary organic aerosols (SOA), or intermediate products) (Fu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They proved the dependence between the traffic and the VOCs concentration. Zhang et al (2019) measured the concentrations of volatile organic compounds during different periods in a district of China. They investigated the sources and the VOCs chemical reactivity using the positive matrix factorization (PMF) model and showed that the highest contribution to VOCs emission was burning coal in the heating period.…”
Section: Introductionmentioning
confidence: 99%
“…There are two procedures commonly used for maintaining IAQ: (i) Ventilation Rate Procedure and (ii) Indoor Air Quality Procedure [9]. The later aims to strike a good balance between energy savings and IAQ.…”
Section: Introductionmentioning
confidence: 99%